2011
DOI: 10.5009/gnl.2011.5.2.200
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Papillary Large Balloon Dilation Combined with Guidewire-Assisted Precut Papillotomy for the Treatment of Choledocholithiasis in Patients with Billroth II Gastrectomy

Abstract: Background/AimsEndoscopic extraction of bile duct stones is difficult and often complicated in patients with a Billroth II gastrectomy. We evaluated a simpler technique to achieve an adequate ampullary opening for the removal of choledocholithiasis using endoscopic papillary large balloon dilation (EPLBD) combined with a guidewire-assisted needle-knife papillotomy.MethodsSixteen patients who had a Billroth II gastrectomy were included in this study. Following placement of the guidewire in the bile duct, a prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 18 publications
(16 reference statements)
2
16
1
1
Order By: Relevance
“…[45678] In the present study, the overall CBD stone removal and complete stone removal rates for first endoscopic session were 96.7% and 90.0%, respectively, which concur with previous studies. [45678] Mechanical lithotripsy is an annoying but essential procedure for the removal of large bile duct stones. The wider ampullary opening made during EPLBD can aid the removal of difficult stones and lower the requirement of mechanical lithotripsy.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[45678] In the present study, the overall CBD stone removal and complete stone removal rates for first endoscopic session were 96.7% and 90.0%, respectively, which concur with previous studies. [45678] Mechanical lithotripsy is an annoying but essential procedure for the removal of large bile duct stones. The wider ampullary opening made during EPLBD can aid the removal of difficult stones and lower the requirement of mechanical lithotripsy.…”
Section: Discussionsupporting
confidence: 92%
“…[5] However, several studies have reported substantially lower rates of post-ERCP pancreatitis after EPLBD in patients with prior B-II gastrectomy (0-5%). [4578] In the present study, only two cases (6.7%) of pancreatitis were observed and both were mild and self-limiting.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…As discussed in previously, there remain concerns about the risk of pancreatitis in patients undergoing EPBD without prior sphincterotomy. An approach that combines limited biliary sphincterotomy with a needle knife over a straight plastic biliary stent or guidewire, followed by EPBD and conventional stone extraction, has been reported 186. It is becoming the method preferred by experts, and potentially combines ease of use, safety and efficacy.…”
Section: Management Of Cbds In Specific Clinical Settingsmentioning
confidence: 99%
“…It is relatively difficult to carry out endoscopic treatment with Roux-en-Y anastomosis and the Billroth II method because of the surgically altered anatomy [8]. The success rate of ERCP using the Billroth II method is lower in patients with choledocholithiasis (63–93%) than in patients with an intact stomach (87–97%) [9].…”
Section: Introductionmentioning
confidence: 99%